"Revealing Divine Wisdom: Examining the Features and Data of the Qur’anic Story" - Hayder Kareem Oudah ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The unique characteristics of the Qur’anic story distinguish it from other narratives, making it a significant subject in the field of Qur’anic studies. It is considered one aspect of the Qur’anic miracle, known as the narrative miracle. This research aims to explore and elucidate the features and information of the Qur’anic story using a descriptive and analytical inductive method. The goal is to emphasize their impact on intellectual, educational, and moral levels and to derive advice and lessons from them. These stories encompass the narratives of the Prophets (peace be upon them) as well as other stories presented in the Qur’an. By understanding and reflecting upon these stories, we can derive contemporary lessons that align with the educational, guiding, and reformative objectives of the message of Muhammad. The Qur’anic story possesses unique qualities and information that enable us to benefit from it in our present lives.